Overexpression of PGC-1α Increases Fatty Acid Oxidative Capacity of Human Skeletal Muscle Cells - Nataša Nikolić; Magdalena Rhedin; Arild C. Rustan; Len Storlien; G. Hege Thoresen; Maria Strömstedt (Biochemistry Research International)
We investigated the effects of PGC-1α (peroxisome proliferator-activated receptor γ coactivator-1α) overexpression on the oxidative capacity of human skeletal muscle cells ex vivo. PGC-1α overexpression increased the oxidation rate of palmitic acid and mRNA expression of genes regulating lipid metabolism, mitochondrial biogenesis, and function in human myotubes. Basal and insulin-stimulated deoxyglucose uptake were decreased, possibly due to upregulation of PDK4 mRNA. Expression of fast fiber-type gene marker (MHCIIa) was decreased. Compared to skeletal muscle in vivo, PGC-1α overexpression increased expression of several genes, which were downregulated during the process of cell isolation and culturing. In conclusion, PGC-1α overexpression increased oxidative capacity of cultured myotubes by improving lipid metabolism, increasing expression of genes involved in regulation of mitochondrial function and biogenesis, and decreasing expression of MHCIIa. These results suggest that therapies aimed at increasing PGC-1α expression may have utility in treatment of obesity and obesity-related diseases.